Identification of ecto and endoparasites in estuarine fish distributed from “El Rosario” to the facilities of “Santa Lucia” Island in the period from July to October 2020 (Nexo Revista Científica, 2022)
In Nicaragua, the knowledge of ecto and endo parasites in both fresh and salt water fish is scarce, having as the only references a study carried out by the Indian and Caribbean University of Bluefields (BICU), and another carried out by the CIDEA, both in the decade of the 90 ', therefore, the initiative arises to carry out this study in the Estuary Venado, located in the community of ¨Las Peñitas¨, in order to identify the main genera of parasites, both external and internal that affect the fish in the area, at the same time, have an updated reference in the west of the country. The study was developed between the months of July to September, having a sampling per month in three different sites of the Estuary, taking as a reference ¨El Rosario¨, until arriving in front of the Santa Lucia Island Facilities, a total of 72 fish, of which 38 fish presented parasites, including horse mackerel, lisa, snook, snapper and palometa, in which 7 genera of parasites were recorded, being the most relevant Ergasilus spp., followed by Capillaria sp., and the fish species with significant incidence is the Lisa in the first place, in turn it was found that of the three sites sampled the one with a high incidence of parasites was La Bocana, which indicates that the greater the human influence near the coasts, the higher the parasitic incidence in fish, since many of the genera have their life cycles in domestic terrestrial species.